Levels and Specific Causes of Stress Perceived by Regular Classroom Teachers - Klas, Leroy D.; Kendall-Woodward, Sharon; Kennedy, Leonie (Canadian Journal of Counselling and Psychotherapy, 2011)
In an attempt to better understand the causes and nature of stress in education, the surveyed 588 regular classroom teachers and 211 specialist teachers. The sample was chosen randomly from stratified divisions of the entire teaching population of Newfoundland and Labrador, and represented ten percent of the actual teaching population. This study focuses on the results pertinent to regular classroom teachers. Respondents reported moderate levels of stress. The nine categories of stressors under study were ranked almost exactly the same by teachers of different grade levels, with Time Management and Parent/Teacher Relations highest. Several areas of significance between teacher groups and biographical factors are reported and discussed.